Analisis Ketaatan Syariah pada Institusi Keuangan Berbasis Syariah - Ansar, Agustan; Abdullah, M. Wahyuddin; Parmitasari, Rika Dwi Ayu (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this study is to evaluate the level of Sharia compliance in Islamic banks in Indonesia by looking at three aspects: Shariah Supervisory Board (DPS), products, and financial statements. According to this study, there are several important issues in the sharia compliance of DPS, including independence, concurrent positions, competence, and sharia audits. When it comes to Islamic bank financing, murabahah is huge, which is due to the depositor paradigm compared to savings, as well as the issue of murabahah being practiced differently from the original concept. This is a very important issue for the product. Finally, it relates to financial reporting such as income smoothing on profit distribution, independent auditors who do not have sharia competence, and the treatment of murabahah margins.